2008
DOI: 10.1590/s0100-40422008000500037
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic mobilization from sulfidic materials from gold mines in Minas Gerais State

Abstract: Recebido em 21/6/07; aceito em 26/10/07; publicado na web em 15/5/08Acid drainage results from exposition of sulfides to the atmosphere. Arsenopyrite is a sulfide that releases arsenic (As) to the environment when oxidized. This work evaluated the As mobility in six sulfidic geomaterials from gold mining areas in Minas Gerais State, Brazil. Grained samples (<2 mm) were periodically leached with distilled water, during 70 days. Results suggested As sorption onto (hydr)oxides formed by oxidation of arsenopyrite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This region has high arsenopyrite contents, FeAsS. 30,31 Frequently, gold is found associated to this mineral, which explain high As and Hg levels in this place.…”
Section: Aqua Regia Pseudo-total Digestion Proceduresmentioning
confidence: 89%
See 2 more Smart Citations
“…This region has high arsenopyrite contents, FeAsS. 30,31 Frequently, gold is found associated to this mineral, which explain high As and Hg levels in this place.…”
Section: Aqua Regia Pseudo-total Digestion Proceduresmentioning
confidence: 89%
“…This region has high arsenopyrite contents, FeAsS. 30,31 Frequently, gold is found associated to this mineral, which explain high As and Hg levels in this place.The samples from BP 036, BP 079, and BP 084 points presented As values between Level 1 and Level 2. Data in 2008 from IGAM (Instituto Mineiro de Gestão das Águas) on the water quality demonstrated that the main contamination sources in these areas (Paraopeba sub-basin) are related to domestic sewage and industrial effluents.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In soils, substrates and tailings from gold mining areas of Brazil, high levels of total As have been measured, e.g., up to 46,493 mg As kg -1 (Andrade et al 2008;Borba et al 2000Borba et al , 2003Deschamps et al 2002;Matschullat et al 2000); however, bioaccessibility tests for this element have not yet been carried out for these areas. In general, such mining areas are quite densely populated regions, with cities located very close to the mines.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenopyrite is the most common sul de mineral, which is generally associated with gold (Au) mining. Its oxidation, dependent on several factors, including the amounts of arsenopyrite, distribution of the size of the ore, temperature, and the time of exposure of the material to water and oxygen (De Andrade et al 2008), produces arsenic oxyacids that facilitate their release into the soil and watercourse (De Andrade et al 2012).…”
Section: Introductionmentioning
confidence: 99%